Cold flow and filterability properties of n-butanol and ethanol blends with diesel and biodiesel fuels. (15th July 2018) - Lapuerta, Magín; Rodríguez-Fernández, José; Fernández-Rodríguez, David; Patiño-Camino, Rayda
Highlights: Bioalcohols contribute to improve cold-flow properties in diesel/biodiesel blends. Butanol blends show better cold-flow properties than less miscible ethanol blends. Phase separation affects differently to cloud, pour cold-filter plugging points. An equation predicts filter plugging of alcohol blends with diesel or biodiesel. Filterability anticipates cold-flow properties as far as blends remain miscible. Abstract: Filter plugging problems caused by some biodiesel components have recently discouraged biodiesel users and suppliers, and triggered normalization actions to limit operability problems in diesel engines. Bioalcohols have proven to be a sustainable alternative as diesel components, although light ones such as methanol and ethanol are limited by their weak miscibility with diesel fuel. Additionally, they have potential to improve the cold flow properties of diesel and biodiesel fuels as far as they remain within the miscible range. With the aim to quantify these improvements, ethanol and n -butanol were blended with diesel and biodiesel fuels showing benefits in cold filter plugging point, cloud point, pour point, freezing point and filterability from certain concentrations. At intermediate alcohol contents, some properties were affected by the formation of a gelatinous phase or by phase separation. For example, immiscible blends led to increases in cloud point and cold filter plugging point, but to decreases in pour point. This information is useful to diagnose separation events in practical blends, and to prevent filter clogging problems. Other n -alcohols were also tested to propose a general equation to predict cold filter plugging point of alcohol blends in diesel and biodiesel blends. Results from filterability test, carried out at ambient temperature, anticipate cold flow problems in miscible blends, but not in immiscible ones.